Gender-Based Violence and Deconstruction Implementation of The Rights Victims on Sexual Violence - Kamilia, Nur (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2024)
This article examines gender-based violence (GBV) as a crucial issue in contemporary society, focusing on the implementation of deconstruction of the rights of sexual violence victims. Through an hollystic and deskriptif- analytical approach, the article explains how patriarchal norms and gender streotypes reinforce a culture of violence, as well as the challenge s faced in protecting victims’ rights. By exploring various policies and best practices, this article aims to provide insights into the strategic steps necessary to create a safe and just environment for victims and to encourage a paradigm  shift in addressing cases of sexual violence. This research is expected to contribute to collective efforts in tackling gender-based violence and supporting the recovery and empowerment of victims.